Rancang Bangun Aplikasi Kalkulator Zakat Berbasis Android Menggunakan Metode Prototype - Khairani Fadhilla; Yolen Perdana Sari (CV. Multi Kreasi Media, 2023)
Information and communication technology is developing very fast. In this case it applies in accordance with the development of an increasingly sophisticated era. Zakat which is usually calculated manually can now take advantage of existing technology with Android. In this development, many things are still not as expected. The problem that often arises is the difficulty of calculating or equalizing the existing zakat, of course, in accordance with Islamic law. Also problems in calculating the distribution of zakat that has been up to one year. Zakat maal or wealth zakat, gold and silver zakat is issued on condition that it reaches the Nishab limit (zakat obligatory limit) and the haul limit (having reached 1 year). Also the problem of paying zakat who do not know the amount of zakat that must be issued, and the lack of awareness of the people who are obliged to pay zakat to issue zakat, so with this the author wants to try to implement it in the form of zakat calculating software. With that, the author is interested in making an android-based zakat calculator application which aims to make it easier to calculate zakat and distribute it. This application is designed using Android Studio and tested using the Black box testing method. Prior to testing, an application demo was held so that the muzakki and amil would know how to operate it. From the results of testing and questionnaires from 20 respondents stated that the application was appropriate to be used as a service medium between amil and muzakki.